Yanomami indigenous emergency through an anti-corruption perspective - de Sá Souza, Marina Marques; Veras Neto, Francisco Quintanilha (Universidad Hemisferios, 2025)
The article investigates the Yanomami indigenous emergency, declared in January 2023 by the Brazilian federal government, through practices of corruption: illegal mining, bribery, capture of public policies, and extortion. The study